LAW ENFORCEMENT AGAINST PERPETRATORS OF CRIMES AGAINST STREET CHILDREN COMMITTED BY THEIR BIOLOGICAL PARENTS - Fajri, Erfan; Suatmiati, Sri; Hayatuddin, Khalisah (Sriwijaya Crimen and Legal Studies, 2024)
Based on the cases in Palembang City, it can be said that law enforcement against perpetrators of crimes against street children committed by biological parents. The formulation of the problem in this study is 1) How is law enforcement against perpetrators of crimes against street children committed by biological parents in the Palembang City Police and 2) What are the factors that influence law enforcement against perpetrators of crimes against street children committed by biological parents in the Palembang City Police? The research method used is a type of empirical juridical research. The sources of data used in this study were primary and secondary data. Based on the results of the study show that law enforcement against the offenders of crimes against street children committed by biological parents in the Palembang City Police Resort, namely by penal measures through imprisonment as in Article 76I Jo Article 88 and Article 76C Jo Article 80 paragraph (1) of Law No. 35 of 2014 concerning amendments to Law no. 23 of 2002, concerning child protection or Article 44 Paragraph (1), Paragraph (4) of the Law of the Republic of Indonesia No. 23 of 2004. Factors that influence law enforcement against perpetrators of crimes against street children committed by biological parents, namely first, the factor of law enforcement officers. Lack of Investigators' Knowledge about Child Protection Law, Second, Community Factors. In cases of crime on the street, children tend to be closed, so it is difficult to socialize with the surrounding environment. Third, cultural factors that do not want to interfere in other people's personal affairs or other people's families or neighbors become a separate problem.